Los títeres para fortalecer el ámbito de convivencia en los niños de preparatoria de la unidad educativa Manuel Cabrera Lozano de la ciudad de Loja, en el periodo 2019-2020. - Hurtado Riofrío, Andrea Stefanía (2021)
The present research work entitled: THE PUPPETS TO STRENGTHEN THE SCOPE OF COEXISTENCE IN THE CHILDREN OF PREPARATORY OF THE EDUCATIONAL UNIT MANUEL CABRERA LOZANO OF THE CITY OF LOJA, IN THE PERIOD 2019-2020. In which the general objective is to strengthen the coexistence environment through the use of puppets for high school children, the research had a qualitativequantitative approach. The methods used were scientific, analytical-synthetic and descriptive; among the techniques and instruments were: the survey addressed to the teachers and the evaluation scale based on the high school curriculum applied to the sample of 21 children. According to the results of the pretest, 72% were found to be at the unachieved level and in part to manage coexistence in the classroom. The teachers surveyed mentioned that puppets are playful and enhance the children's imagination, helping their personal and social development in the teaching-learning process. To contribute to the solution of the problem observed, a guide of activities based on puppets was elaborated which allowed strengthening the coexistence environment, verifying at the end of this that 76% of the children raised the coexistence environment to the achieved level. After the intervention with the alternative proposal, it was evidenced that it had a positive impact on the development of coexistence, demonstrating that the use of puppets in the classroom favors communication, participation, expressions, rules of respect, among classmates and teachers.